Transformation of language and stylistic means of creating artistic images in the artistic heritage of Yakov Struhmanchuk (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article deals with the artistic world of talented graphist, artist, caricaturist, portraitist, fine art expert Yakiv Strukhmanchuk. Works of I. Franko, Yu. Lotman, F. Pogrebennyk and others make the methodological basis of the investigation. Based on the caricatures on M. Grushevskyi, M. Kozoris, D. Rudyk, D. Zagul, M. Kichura and others that were accompanied by the text comments of V.Shvorka, non-verbal works have been analized with much attention being concentrated on the artistic detail that carries out considerable emotional and meaning yield.
Keywords: Ya. Strukhmanchuk; V. Shvorka; intermediality; caricature; fine arts; paratext